Anxiety and Depression in Newly Diagnosed Epilepsy: A Matter of Psychological History? - Forthoffer, Natacha; Tarrada, Alexis; Brissart, Hélène; Maillard, Louis; Hingray, Coraline (Frontiers in Neurology, 2021)
Purpose: Anxiety and depression are highly prevalent in patients with epilepsy and these symptoms can even precede the onset of the pathology. We aimed to define the prevalence of anxiety and depressive symptoms at the time of the epilepsy diagnosis and the factors related to their presence in newly diagnosed adult patients. Methods: One hundred and twelve newly diagnosed patients were assessed, usually in the week following diagnosis. Patients were untreated at this time. We used the Neurological Disorders Depression Inventory for Epilepsy (NDDI-E, cut-off ≥ 15) and the Generalized Anxiety Disorder 7-Item scale (GAD-7, cut-off > 7). A semi-structured interview was conducted to collect sociodemographic and epilepsy data and patients’ psychiatric history. We first compared patients with and without anxiety symptoms, then patients with and without depressive symptoms. Results: According to the GAD-7 scale, the prevalence of anxiety symptoms at the time of diagnosis was 35%. Patients with anxiety symptoms had significantly more psychiatric history (26%, p=0.001) and more history of psychological trauma (51%, p=0.003) than patients with no anxiety symptoms. According to the NDDI-E scores, the prevalence of depressive symptoms at the time of the diagnosis was 11%. Patients with depressive symptoms had significantly more psychiatric history (43%, p<0.001) and more history of psychological trauma (65%, p=0.007) than patients with no depressive symptoms. No difference between groups was found for other sociodemographic variables (age and gender), epilepsy characteristics (number of seizures prior to diagnosis, time from first seizure to diagnosis, type of epilepsy and localisation in focal epilepsy) or neurological comorbidities. Conclusions: Anxiety symptoms are common while depressive symptoms are less prevalent at the time of diagnosis. It appears essential to be aware of anxiety and depression in newly diagnosed epileptic patients. They should be screened and routinely monitored, especially those patients with a history of psychological trauma and/or psychiatric disorders. Longitudinal follow-up is required to identify whether these factors and anxiety and depression themselves have an impact on the future course of care.